SITUS INVERSUS TOTALIS: AN OVERVIEW OF THE MIRROR IMAGE - Pavlović Stojanović, Jasmina; Perović, Aleksandra; Stojanović, Minja; Margitin, Nenad; Milenković, Ivona; Lazić, Ljiljana; Antonijević Đorđević, Dragana; Bjelica, Magdalena (Srpski medicinski časopis Lekarske komore, 2023)
Introduction: Situs inversus totalis (SIT) is a rare phenomenon and the incidence of this condition ranges from 1:10.000 to 1:20.000 people. It is a condition in which the arrangement of internal organs is a mirror image of normal anatomy. It can occur independently or as part of a syndrome with other abnormalities. Congenital heart defects are present in about 5-10% of such individuals. The underlying cause and genetics of situs inversus are complex. Case report: A 69-year-old female patient was referred to the Department of General Surgery in May 2023 for ventral hernia surgery. This was her third admission to the same department; in 1998, she had appendectomy, and in 2018, the patient underwent a cholecystectomy due to gallbladder calculus. Upon admission, the patient was referred for a CT scan of the thorax and the abdomen, in order to confirm the correct anatomy, given that she was already familiar with her condition and the existence of situs inversus. During the CT examination, the arrangement of the abdominal organs was confirmed as a mirror image of normal anatomy with the heart on the right side of the chest. Conclusion: Most people with SIT live completely normal lives. Life expectancy and risk of acquired diseases are similar to those of the general population. In a certain number of cases, there is a connection with certain pathological entities. In patients with SIT, common causes of acute abdominal pain often lead to wrong conclusions, and the localization of the cause of abdominal pain is extremely complicated and difficult. Identifying people with SIT makes it possible to reduce risks during surgical procedures and interventional procedures.